Effect of Workload, Compensation, and Motivation on Employee Performance at Madani Medan General Hospital - Khairunnisa, Zhafira Amriyatti; Bahri, Syaiful; Effendy, Sjahril (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to examine and analyze the effect of workload, compensation and motivation on employee performance at Madani Medan General Hospital. The approach in this assessment is to use a deskriptif and associative approach. In this study, the population was employees at Madani Medan General Hospital, totaling 60 medical personnel, because the number of population used as a sample amounted to 60 medical personnel. The analysis of this research is multiple linear regression. The results showed that workload has a significant effect on employee performance. Compensation has a significant effect on employee performance. Motivation has a significant effect on employee performance. Simultaneously workload, compensation, and motivation have a significant effect on employee performance.